Relate North 11 : Beyond Borders : Stitching Light through Boundary Lines, 2023:collaborative embroidery; wool fabric, hand-dyed local wool yarn - Kovero, Minna; Kravtsov, Tatiana (University of UMEA, 2023)
Materials: wool fabric, hand-dyed local wool yarn Artist names: Minna Kovero and Tanya Kravtsov together with the group members: Natalia Tsyrtsaki, Margarita Diachuk, Liuba Balysheva, Zoya Nekrasova, Tatiana Horodnyk, Svetlana Ustymenko, Liubov Takiianuzova The artwork is a collaborative embroidery made with newcomers from Ukraine who fled the war and based their lives in Rovaniemi, Finland. The art piece is made into the form of patchwork garment and as a whole it explores revitalisation of the sun symbolism and its empowering aspects. The crafting aims to create connectedness between people reaching each other's sunrays in the fabric of multiculturalism. While crafting together we share stories, memories and images related to the sense of place and aspects of darkness and light experienced by us living in the North. We explore the sun symbolism and female sun goddesses that have crossed borders and generations from Ukraine to Karelia and the Arctic. By stitching personal stories and memories together we make a connection to a broader sense of place.